4x^2-10=90

Simple and best practice solution for 4x^2-10=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x^2-10=90 equation:


Simplifying
4x2 + -10 = 90

Reorder the terms:
-10 + 4x2 = 90

Solving
-10 + 4x2 = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 4x2 = 90 + 10

Combine like terms: -10 + 10 = 0
0 + 4x2 = 90 + 10
4x2 = 90 + 10

Combine like terms: 90 + 10 = 100
4x2 = 100

Divide each side by '4'.
x2 = 25

Simplifying
x2 = 25

Take the square root of each side:
x = {-5, 5}

 

See similar equations:

| 9w-w^3= | | 4x^2-15x+9= | | y(7+k)=0 | | 4(7x-4)= | | 12x-2=28x+10 | | 6x^2+x-12= | | -2(3x-3)=2x | | 4(3Y-1)-3(2Y)=12 | | -24-a=15 | | 4x^2+22x= | | 5z-17=13 | | x^2+10x+19=0 | | -4(X-7)-3=25 | | 9h+4=6h-2 | | x-25=47 | | 3-3(A-1)=2+9 | | 22=4+6e | | 4a^2(3a-3b)= | | 3.85+x=15.27 | | 13-2(A-1)=6+9 | | 2ln(x+1)+ln(3x+5)+ln(2)=ln(6x+1)+ln(x-2)+ln(x-2) | | 12a^2+12a-6=0 | | 2-2(A-1)=1+9 | | 7(1x+8)=42 | | 20m^2-7m-3= | | 180-x=3(90-x) | | 10+-3=57 | | 1x-3=3x-5 | | 7X+2=-2+2X+29 | | p+(p+28)+(3p-35)=538 | | x^2+9x-33=0 | | 2log(x+1)+log(3x+5)+log(2)=log(6x+1)+log(x-2)+log(x-2) | | -15=2r+1 | | .9(7x+9)=5.2-(x-3) | | x+48-37=100 | | 2(x+3)+9=15 | | 4(5z-1)-3(z+8)=3(z+1) | | -27=-7-4c | | 8-5c=-37 | | 5(x+1)=2 | | 10(n+9)=2(45+5n) | | 5x+8-2x=36 | | 6(1x+8)=48 | | 7x^3y^2(3x+3y)= | | -8-9y=16 | | 11=18+7f | | 3(2m-4)=8m-6m | | -67-11x=142 | | 3(x-7)+6=3x+8 | | 10x+23=-67 | | 4x=3x+4 | | (3x)2y=8-x | | 2(x+8)=3(x-9) | | 2x-3=18x+5 | | 7y-5=6y-8 | | 8-5*C=-37 | | 10=4-3x | | 7-(x+3-4)=3(x+1)-39 | | y^2-49= | | y-3.021=6.979 | | -4y-21=5 | | 13x-(8x-5)=35 | | 46-8x=-18 | | 3u^2v^2(2u-7v)= | | 2y+18=4y |